Exploring Master's Students’ Self-Efficacy in Speaking English During Hybrid Learning - Yohanes Bagas Nur Setiawan; Paschalis Kurniawan Sanjaya; Martinus Hergirico Riandana; Concilianus Laos Mbato (JET (Journal of English Teaching), 2025)
In the post-pandemic situation, where hybrid learning has become prevalent, effective communication between lecturers and students is very important. Self-efficacy is a crucial factor that affects their communication or speaking in class. Nowadays, research on students’ self-efficacy in speaking has received considerable attention among researchers. However, Self-efficacy in hybrid learning, particularly with a focus on master’s students, remains an underexplored area of research. To fill in the gaps, the researchers aim to know what factors and challenges influence students’ self-efficacy in speaking during hybrid learning. The participants were six English Education Master’s students at Sanata Dharma University. Guided by Bandura’s Social Cognitive and Self-Regulation Theories, this research employed a descriptive qualitative method. Data was collected through in-depth interviews and observations and analyzed using thematic analysis via QDA Miner Lite. The steps consist of transcribing, coding, grouping, and then interpreting the data. The findings showed that some factors that influence students' self-efficacy in speaking are motivation, learning, social environment, and role models. On the other hand, factors that inhibit students' self-efficacy in speaking, namely speaking anxiety, low confidence level, and low content mastery. The research limitations include six participants from specific study programs, limiting generalizability to other contexts or institutions.